2020
DOI: 10.1017/dsd.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Model for Product Service Systems of Systems

Abstract: A Product Service System of Systems (PSSoS) is a set of products, services, infrastructure, and a network where its constituent elements exhibit operational and managerial independence. As such, a PSSoS shows PSS characteristics of heterogeneity and evolvability and SoS characteristics of emergence and diversity. Neither existing PSS nor SoS development approaches fully address these characteristics. Thus, PSSoS development raises new challenges. In this paper, we propose a PSSoS meta-model that integrates PSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…In this section, we aim to quantify the importance and the influence of each PSSoS stakeholder in business partnerships and development. [54][55][56] The literature review showed that quantitative stakeholder analysis approaches give various interpretations…”
Section: Analyzing Pssos Stakeholder Importance and Influence In Busi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we aim to quantify the importance and the influence of each PSSoS stakeholder in business partnerships and development. [54][55][56] The literature review showed that quantitative stakeholder analysis approaches give various interpretations…”
Section: Analyzing Pssos Stakeholder Importance and Influence In Busi...mentioning
confidence: 99%
“…In this section, we aim to quantify the importance and the influence of each PSSoS stakeholder in business partnerships and development 54–56 . The literature review showed that quantitative stakeholder analysis approaches give various interpretations of the importance or influence of stakeholders depending upon the definition of a stakeholder, the type of information, and the objective (e.g., energy efficiency).…”
Section: Analyzing Pssos Stakeholder Importance and Influence In Busi...mentioning
confidence: 99%
“…SoS development is described as the expansion of the thinking beyond the boundaries of independent systems and how the combination of the functions of individual systems can be synthetized to create a new functionality. Different SoS frameworks include functional representations for SoS (Fakhfakh, Hein, Chazal, & Jankovic, 2020) . For instance, functional chains represent functions and their logical and execution relationships (including information and energy flows for example).…”
Section: Sos Functional Dependency Matrix and Network Definitionmentioning
confidence: 99%
“…Currently, the Construction Equipment domain is undergoing paradigm shifts from hardware-intensive machinery products towards software/data intensive integrated mechatronic information systems. The latter are complex System-of-Systems (SoS) (Maier 1998) referred to as Product Service Systems (PSS), where the physical product is part of a much larger entity, consisting of other physical products as well as information systems, providing "capabilities" and "services" beyond the scope of the functionality of a single product (Fakhfakh 2020). Capabilities can be summarized as "the power or ability to do something" and are attributed to systems or SoS (Martin et al 2022).…”
Section: Introductionmentioning
confidence: 99%